2020
DOI: 10.1016/j.ijrobp.2019.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patient-Reported Outcomes After High-Dose Chemoradiation Therapy for Nonsurgical Management of Distal Rectal Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…10,15,24 This exploratory analysis supports favourable longer-term patient-reported outcome scores seen at 1-year, 2-year, and 5-year follow-ups after organ preservation in various trials. 10,33 Our data provide an important contribution to the literature due to the absence of published randomised studies comparing patient-reported outcomes following total mesorectal excision and organ preservation. Although an unexpected finding, the lower baseline mean scores in a number of function items for the radical surgery group (completed after knowledge of randomisation status) might reflect our impression that the perceived risks of surgery in early-stage rectal cancer are higher than patients desire.…”
Section: Discussionmentioning
confidence: 96%
“…10,15,24 This exploratory analysis supports favourable longer-term patient-reported outcome scores seen at 1-year, 2-year, and 5-year follow-ups after organ preservation in various trials. 10,33 Our data provide an important contribution to the literature due to the absence of published randomised studies comparing patient-reported outcomes following total mesorectal excision and organ preservation. Although an unexpected finding, the lower baseline mean scores in a number of function items for the radical surgery group (completed after knowledge of randomisation status) might reflect our impression that the perceived risks of surgery in early-stage rectal cancer are higher than patients desire.…”
Section: Discussionmentioning
confidence: 96%
“…Whether this represents a relevant parameter in the context of organ preservation in rectal cancer needs to be addressed in future investigations. Interestingly, rectal bleeding was one of the dominant late toxicities in a prospective study on dose escalated radiotherapy using a brachytherapy boost to a total dose of 65 Gy [36]. Regarding anal sphincter function, in a retrospective study of patients with LARC [37] a series of dosimetric parameters was correlated with loss of sphincter function.…”
Section: Discussionmentioning
confidence: 99%
“…Brachytherapy does not form part of the standard multimodal approach to rectal or anal cancer. However, organ preservation approaches to lower GI tumours have explored dose escalation with brachytherapy as an alternative to surgical management with encouraging results [38,39]. The main indication for brachytherapy in the elderly population with ano-rectal tumours is in those who are unfit for standard care with palliative options being offered for inoperable, locally advanced and recurrent disease.…”
Section: Rectal Cancermentioning
confidence: 99%